The role of synovial mesenchymal stem cell-derived exosomes in cartilage repair: a systematic review - Su, Jiemao; Qi, Yansong; Niu, Lin; Wang, Yongxiang; Wei, Baogang; Ma, Bingxian; Kong, Keyu; Zhai, Zanjing; Xu, Yongsheng (Frontiers in Pharmacology, 2025)
BackgroundKnee osteoarthritis (KOA) is the most widespread degenerative disease in the cumulative population. With the increasing aging of the population, KOA has become one of the most important factors leading to joint deformities in middle-aged and elderly people. At present, the therapeutic effect of synovial mesenchymal stem cells (SMSCs) has gradually attracted the attention of many researchers. Due to their better chondrogenic ability, they have gradually become an effective way to treat cartilage injury. Because its function mainly relies on exosomes and exosomes have many advantages of cell-free therapy, it has attracted much attention from researchers.MethodsThe study was searched between April 20, 2014, and April 20, 2025, on China National Knowledge Infrastructure (CNKI), Wanfang database, PubMed, the Cochrane Library, and Web of Science. Two researchers independently reviewed the literature, extracted data, evaluated bias. In cases of disagreement, a third reviewer made the final decision.ResultsThe initial literature search identified 198 potentially relevant studies. After removing 7 duplicate publications, 183 records remained for screening. Title and abstract review excluded 164 irrelevant studies. Full-text assessment was performed on the remaining 19 articles, of which 12 ultimately qualified for inclusion. Overall, the risk of bias in most of the eligible studies was unclear. In the 12 included studies, it was confirmed that SMSC-derived exosomes could maintain and promote cartilage repair and reduce the degree of cartilage damage by in vitro cell experiments. By isolating and extracting the main functional mirnas, it was found that these functional mirnas had a good therapeutic effect on cartilage injury.ConclusionSMSC-derived exosomes demonstrate significant potential for cartilage repair in KOA, primarily mediated by functional miRNAs. While in vitro results are promising, the unclear risk of bias in current studies underscores the need for higher-quality clinical research to validate their therapeutic application.Systematic Review Registrationidentifier [CRD420250651715].